Evolution and textual quantitative analysis of China’s palliative care policies: a three-dimensional analytical framework approach - Wang, Lele; Zhao, Shan; Xing, Furong; Zhang, Hanlu; Qu, Lei; Li, Dongli; Ji, Jingmin; Ye, Jianya (Frontiers in Public Health, 2025)
BackgroundTo summarize the evolution trend of China’s hospice policy, dissect the possible instrumental problems of the policy, and provide reference for the optimization and improvement of China’s hospice policy.MethodsPolicy document analysis was used to encode and examine palliative care policy texts. The use of policy tools was assessed across three dimensions: policy types, participating entities, and temporal trends.ResultsA total of 36 policy documents were analyzed. In the X dimension, 253 codes were identified, with environmental, supply, and demand policy tools comprising 57.71, 23.32, and 18.97%, respectively. In the Y dimension, 423 codes were identified, with government agencies, medical institutions, social organizations, and healthcare professionals comprising 73.05, 18.44, 4.96, and 3.55%, respectively. In the Z dimension, 253 codes were identified, corresponding to three stages: initial exploration (10.67%), in-depth exploration (14.62%), and pilot implementation (74.70%).ConclusionPalliative care in China is gradually advancing. However, policy tools remain imbalanced, with a strong emphasis on environmental tools over demand-side tools, leading to internal structural inconsistencies. The allocation of policy tools among stakeholders is also uneven, characterized by a single-entity dominance and a government-driven supply model. It is recommended that policies be aligned with their developmental stages, the structure of policy tools be optimized, balanced utilization among stakeholders be ensured, and role differentiation and collaboration enhanced.